Robust edge states in amorphous gyromagnetic photonic lattices - Mansha, Shampy (2018)
We numerically study amorphous analogs of a two-dimensional photonic Chern insulator. The amorphous lattices consist of gyromagnetic rods that break time-reversal symmetry, with the lattice sites generated by a close-packing algorithm. The level of short-range order is adjustable, and there is no long-range order. The topologically nontrivial gaps of the photonic Chern insulator are found to persist into the amorphous regime, so long as there is sufficient short-range order. Strongly nonreciprocal robust transmission occurs via edge states, which are shown to propagate ballistically despite the absence of long-range order, and to be exponentially localized along the lattice edge. Interestingly, there is an enhancement of nonreciprocal transmission even at very low levels of short-range order, where there are no discernible spectral gaps.